Critical Reflection into Action: Facilitating Conditions of Antiracist Action among White Youth in the Netherlands. - de Bruijn, Ymke (Journal of Youth & Adolescence, 2025)
Critical reflection is a necessary yet not sufficient prerequisite for critical action, but little is known about conditions that facilitate associations between the two. This study investigates when associations between critical reflection on racism and antiracist action among White youth in the Netherlands are stronger, examining critical motivation, parental ethnic-racial socialization, and intergroup friendships as facilitating conditions. 338 17–21-years old White youth (M = 19.44, SD = 1.28, 73% female) participated in a survey study. The identified positive association between critical reflection and action was stronger for youth with higher levels of critical motivation. Parental ethnic-racial socialization and intergroup friendships, in contrast, did not moderate the association. Boosting critical motivation seems a promising avenue to fostering antiracism among White youth.